Direct Gaze Holds Attention, but Not in Individuals with Obsessive-Compulsive Disorder - Mario Dalmaso; Lara Petri; Elisabetta Patron; Andrea Spoto; Michele Vicovaro (Brain Sciences, 2022)
The attentional response to eye-gaze stimuli is still largely unexplored in individuals with obsessive-compulsive disorder (OCD). Here, we focused on an attentional phenomenon according to which a direct-gaze face can hold attention in a perceiver. Individuals with OCD and a group of matched healthy controls were asked to discriminate, through a speeded manual response, a peripheral target. Meanwhile, a task-irrelevant face displaying either direct gaze (in the eye-contact condition) or averted gaze (in the no-eye-contact condition) was also presented at the centre of the screen. Overall, the latencies were slower for faces with direct gaze than for faces with averted gaze; however, this difference was reliable in the healthy control group but not in the OCD group. This suggests the presence of an unusual attentional response to direct gaze in this clinical population.